Towards platform pedagogies: why thinking about digital platforms as pedagogic devices might be useful. - Sefton-Green, Julian (Discourse: Studies in the Cultural Politics of Education, 2022)
In a context where current forms of governance and polity across many societies are engaging with 'platformisation', the paper argues that the utility and consequences of using a theory of pedagogy can provide a different way to explain how digital technology might 'determine' subjectivity. This paper describes the key process of how platforms work when considered as a 'pedagogic device': paying particular attention to how users 'learn' or are 'subjected' to norms and behaviours. It outlines three key dimensions of pedagogicisation, textualisation, templatisation and trainability arguing that digital platforms suggest an eternal process of school enrolment – a classroom we can never leave, a form of certification to which we aspire. To re-work Plantin, J. C., Lagoze, C., Edwards, P., & Sandvig, C. [(2018). Infrastructure studies meet platform studies in the age of Google and Facebook. New Media and Society, 20(1), 293–310.] formulation, it articulates a platformisation of pedagogy as much as a pedagogicisation of platforms thus concluding how the process of platformisation itself is part of a wider inscription into forms of pedagogic authority.